A double membership: minors and adults with disabilities from migratory routes - Andrea Canevaro (University of Bologna, 2020)
Inclusion is ecosystem. We should learn from empowerment. A human being who comes into the world with a disability, or who, growing up, seems to have Special Needs, must be able to develop his own project. That he has to lean on the project of the adults who live next to him. We all need a project. The migrant above all wants to look for a better life. Who brings a problem can also bring a resource. Design together. Discover the passion of an adult human being. Intertwining one's passion, the bonds of belonging and the data of reality.